The Significance of Work Motivation: The Impact of Organizational Culture and Work Environment on Employee Performance - Nugraha, Bambang Achmad; Soelistya, Djoko; Desembrianita, Eva (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The objective of this study is to ascertain and examine the impact of Organizational Culture and Work Environment on Employee Performance, with Work Motivation serving as an intermediary factor. This study employs quantitative methodologies. The study sample included all individuals employed by the hospital. The study used a purposive sampling strategy, specifically targeting personnel who were neither general practitioners nor specialists. The whole study sample consisted of 130 participants. Statistical tests were conducted using path analysis with the SEM-PLS software 4. Source of information: Primary data was collected by the distribution of questionnaires, which were sent to and returned from 130 respondents. The findings of this study suggest that both Organizational Culture and Work Environment have a favorable and substantial direct impact on employee performance. Work has a favorable and substantial direct impact on motivation, and work motivation in turn exerts a favorable and substantial direct impact on employee performance. The impact of organizational culture on employee performance is mediated by motivation. This mediation is fully positive, as the indirect influence of organizational culture through motivation is greater than its direct influence. Similarly, the work environment affects performance through motivation, with the mediation being fully positive as well, as the direct influence is stronger. Given its limited indirect impact, it is desirable for Gresik Hospital to maintain and enhance a good corporate culture, while also striving to provide a favorable work environment that fosters motivation and ultimately maximizes employee performance.